DISAGGREGATED TRADE OPENNESS ON SHADOW ECONOMY IN NIGERIA: DOES INSTITUTIONAL QUALITY MATTER? - Adegboyega, Soliu Bidemi; Ogede, Jimoh Sina; Odusanya, Ibrahim Abidemi; Ajayi, Felix Odunayo; Atoyebi, Olayinka E. (Jurnal Ekonomi dan Bisnis Airlangga, 2022)
Introduction: It is likely that enterprises and entrepreneurs will be encouraged to engage in the formal sector as economies integrate more fully into the global economy. Thus, we begin our investigation by looking at the relationship between Nigeria's shadow economy and disaggregated trade openness. Based on Nigeria's inadequate institutional quality, our second purpose is to conduct further research on the role institutional quality plays in moderating the relationship between its shadow economy and disaggregated trade openness between 1991 and 2018. Methods: The fully modified ordinary least squares (FMOLS) and Granger causality methods are used in this paper to investigate the nexus and causal effect in time-series analysis. Results: The coefficients of institutional quality, import-to-GDP ratio, government expenditure, and financial development all have an adverse impact on Nigeria's shadow economy. The inflation proxy with the consumer price index, economic growth, and the export-to-GDP ratio all improve Nigeria's shadow economy. The findings of interaction between the import-export ratio and the quality of institutions positively affect the Nigerian shadow economy. The pairwise Granger causality exercise comes after the regression analysis. Conclusion and suggestion: The study concludes that the size of Nigeria's shadow economy is influenced by institutional quality, import trade, government expenditures, and financial development. Similarly, we find no causal relationship between disaggregated trade openness in Nigeria and institutional quality. As a result, policymakers and the country's government must act quickly and decisively to reduce the impact of informal activities on the country's economy.